Improving The Students’ Speaking Skill Through Storytelling Technique Toward Eleventh Grade Students At SMK Swasta Cimanggis - Megawati Megawati (STKIP PGRI Tulungagung, 2018)
The purpose of the research was to improve students’speaking skill through storytelling technique toward eleventh grade students at the first semester 2016/2017 academic year of SMK Swasta Cimanggis Depok. The researcher applied qualitative research, a classroom action research. This research used three cycles. Each of cycle consisted of planning, acting, observing , and reflecting. The subject of the research was the eleventh grade students of SMK Swasta Cimanggis in academic year 2016/2017 that consisted of 22 males and females. The researcher collected data using observation, test, and discussion that was needed at the time of research. This research employs describe the process in which the researcher using teaching speaking especially in English speaking. The result research in Improving the Students’ Speaking Skill Through Storytelling Technique showed an increasing percentage and average score. Cycle 1 was 45% or the average score of 66,40, in cycle 2 was 77% or the average score of 73,22, in cycle 3 was 91% or the average of 75,61. It proved that students’ speaking skill taught by storytelling seemed to increase.